Enhanced Magnetic Microwave Absorption at Low‐Frequency Band by Ferrite Assembled Microspheres with Controlled Components and Morphologies. Issue 8 (22nd June 2021) - Huang, Mengqiu; Yu, Xuefeng; Wang, Lei; Liu, Jiwei; You, Wenbin; Wang, Min; Che, Renchao
Abstract : Because of the frequency‐dispersion characteristic, electromagnetic wave energy dissipation depends mainly on the magnetic loss at low frequency (S‐band, 2–4 GHz). Herein, a strong magnetic microsphere is constructed via a simple spray drying and subsequent calcination process. With the reaction temperature increasing, the microparticles are forcibly assembled by different contents of ferrite crystallites and Fe metal (mainly containing Fe2 O3, Fe5 O12, FeO, and Fe), accompanying morphology evolution. Attributed to the component and microstructure controlling, the permeability parameters of the heterogeneous ferrite composite microspheres (HFCOMP) can be considerably promoted, contributing to the optimized impedance matching in S‐band. As expected, the maximum reflection loss (RLmax ) of HFCOMP is enhanced to −41 dB in S‐band, and the effective absorption bandwidth (EAB) is widened to 1.52 GHz (equivalent to 75% of the S‐band). The HFCOMP can achieve an RLmax of −53.5 dB at only 2 mm in X‐band. Observed by electron holography, the series of HFCOMP composites show the visual magnetic coupling effect, which boost the magnetic responding ability. Therefore, this study provides a guideline value for microstructure design in low‐frequency absorption. Abstract : The unique heterogeneous microspheres forcibly assembled by different contents of ferrite crystallites and Fe metal can achieve remarkable microwave absorption performance in 2–4 GHz, accompanying with several morphology evolutions. The enhanced reflection loss values and effective absorption band are mainly abscised to the boosted magnetic dissipation and hierarchical interface polarization.